Dispensasi Kawin dan Perceraian Usia Anak: antara Realitas Sosial dan Tekstual Hakim - Yulmitra Handayani; Fika Aufani Kumala; Muhammad Al Mansur; Juwandi (Fakultas Syariah IAIN Madura, 2023)
This study responds to the Determination of marriage permits by the Jember Religious Court which was accompanied by a Divorce Decision submitted by the same party in a short period of time. Child divorce is the result of hasty marriages, without knowing more about the holistic and substantive meaning of marriage. Methodologically, this study uses a sociological normative approach with primary data on the decisions and decisions of judges at the Jember Religious Court and reduces various cases of child marriage which result in divorce at a young age. The result is that the judge uses the diction